SISTEM INFORMASI MANAJEMEN PEMESANAN PADA PERCETAKAN DOUBLE D MAKASSAR - Ryantomo; Sudirman; Marlina (JTRISTE, 2019)
This study aims to design and build a system that can be implemented on a computerized system to optimize the workings of the company Double "D" printing Makassar, where this study uses the Linear Sequence method. The test uses the Black Box testing method with the results of the test can be printed reports that can be printed according to the period and the program has been running according to the research objectives. With this new computer-based system it is expected that Double D Printing owners can run the printing order process.